The Impact of Unplanned School Closures on Adolescent Behavioral Health During the Covid-19 Pandemic in Malaysia - Amran, Muhammad Syawal; Jamaludin, Khairul Azhar (Frontiers in Public Health, 2021)
School closures were implemented as a public health intervention to reduce the risk of infection from COVID-19. However, prolonged school closure is likely to impact adolescents’ behavioral health due to the extreme change in routine. The current study aimed to explore adolescents' behavioral health experiences during the beginning of the outbreak of the COVID-19 pandemic. This study was done using qualitative methods to interview 15 adolescent participants (n=15) from low-income households in Malaysia. The study lasted for two months amidst the outbreak and data were collected via online based on focus group discussions. The results revealed that adolescents faced four main themes of experience during the COVID-19 pandemic: Alteration of sleep patterns, stress-related fatigue, dysfunctional eating patterns and lack of physical activity. This first-hand experience shows that knowledge and skills of adolescents’ behavioral practices during outbreak deserves attention. This research stresses the role of family, schools, and media in addressing the health communication gap among adolescents to help them adapt in these new norms